On influence of face sheet distributions on low-velocity impact failure of metal honeycomb core sandwich plates. (January 2023) - Qin, Qinghua; Chen, Shangjun; Bai, Chunyu; Wang, Yongbin; Zhang, Wei
Abstract: The influence of face sheet distributions on failure and energy absorption of metal sandwich plates with aluminum honeycomb core subjected to low-velocity impact is investigated experimentally and numerically. A fair comparison of three types of asymmetric sandwich plates with an equal area density is made by changing the thickness distribution of upper and lower face sheets. The low-velocity impact experiments are performed and the active failure modes are obtained. The finite element (FE) simulations are conducted and agree well with the experimental results. The energy absorption mechanism of sandwich plates is identified and explored with aid of the FE simulations. It is shown that the thickness distributions of upper and lower face sheets have significant effects on dynamic response, failure mode and energy absorption distributions of the sandwich plates. Highlights: Low-velocity impact of asymmetrical metal honeycomb sandwich plates was considered. Failure modes and dynamic response characteristics were obtained experimentally. An effective numerical model was validated by experimental results. Influence of face sheet distribution on failure and energy absorption was revealed.